2022
DOI: 10.1371/journal.pone.0267958
|View full text |Cite
|
Sign up to set email alerts
|

Brood reduction caused by sibling cannibalism in Isodontia harmandi (Hymenoptera: Sphecidae), a solitary wasp species building communal brood cells

Abstract: Sibling rivalry or brood reduction prevailing within bird nests is effectively avoided in solitary aculeate nests because the larvae of wasps and bees usually develop in each brood cell. However, a solitary wasp species, Isodontia harmandi, allows us to study brood reduction in a communal brood cell, where up to a dozen larvae develop in a group relying on prey provisioned by a female wasp. To demonstrate brood reduction in this species, we collected nests at various developmental brood stages from fields for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…In this study we first determined whether the larval cannibalism of I. harmandi is induced by prey shortage. Although our previous study showed that per capita prey provision was smaller in large broods and that cannibalistic events occurred more frequently in large broods (Imasaki and Endo 2022), the occurrence of cannibalism was not related directly to the amount of prey. Here, we experimentally examined the likelihood of cannibalism in pairs of wasp larvae under controlled conditions with different levels of prey availability in artificial nest chambers.…”
mentioning
confidence: 60%
See 4 more Smart Citations
“…In this study we first determined whether the larval cannibalism of I. harmandi is induced by prey shortage. Although our previous study showed that per capita prey provision was smaller in large broods and that cannibalistic events occurred more frequently in large broods (Imasaki and Endo 2022), the occurrence of cannibalism was not related directly to the amount of prey. Here, we experimentally examined the likelihood of cannibalism in pairs of wasp larvae under controlled conditions with different levels of prey availability in artificial nest chambers.…”
mentioning
confidence: 60%
“…Female wasps of Isodontia harmandi build a nest in pre-existing holes, such as abandoned beetle tunnels and the cut ends of horizontally piled bamboo canes (Tsuneki 1963). They use several prey species from among the tettigoniid insects as food for their larvae (Iida 1934, Iwata 1936, Tsuneki 1963, Imasaki and Endo 2022). Females lay an egg on the first prey (pedestal prey) brought into a cavity closed with a loose temporary plug, and repeat the prey-hunting and egg-laying cycle a few to a dozen times within the same brood cell.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations